The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2150131917714929
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Primary Care: Impact on Depression Outcomes Within Collaborative Care

Abstract: Background:Individuals with personality disorders (PDs) are high utilizers of primary care and mental health services; however, they struggle to utilize the care effectively and studies have shown a strong association between having a PD and higher impairment in social role functioning. This is especially important because PDs are highly comorbid with a wide range of other mental health disorders. The collaborative care model (CCM) for depression was developed with an emphasis on patient engagement and aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…Our study indicates that the validity of the SI-Bord is similar to other psychological measurements and one interpretation of our results is that a high score on the SI-Bord, is, as expected, associated with a higher level of depression and perceived stress and a lower level of perceived social support, which is consistent with other related studies [11,50]. This underscores the importance of detecting BPD early.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study indicates that the validity of the SI-Bord is similar to other psychological measurements and one interpretation of our results is that a high score on the SI-Bord, is, as expected, associated with a higher level of depression and perceived stress and a lower level of perceived social support, which is consistent with other related studies [11,50]. This underscores the importance of detecting BPD early.…”
Section: Discussionsupporting
confidence: 92%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, fth edition (DSM-5), BPD is characterized by 'a pervasive pattern of instability of interpersonal relationships, self-image, and affects, and marked impulsivity beginning by early adulthood and present in a variety of contexts' [10]. BPD is closely related to depression [11][12][13] and the unstable moods, impulsivity and violent behaviour characteristic of BPD make it highly correlated with suicide attempts [14]. BPD is also associated with poor social support [15].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that there is a lack of personality and anxiety disorder comorbidity assessments in patients treated for depression in current Swedish secondary psychiatric care. This shortcoming demands attention, as earlier studies have shown that without a thorough assessment, psychiatric comorbidity may go unrecognized [24] and that personality disorders as well as anxiety disorder comorbidities affect the treatment outcome of depression [8,10,13,14,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“… 13 - 15 Also, a prior study in our institution demonstrated that within CCM, patients with PD were able to achieve remission only 25.0% of the time by 6 months compared with a 54.3% remission rate for patients without PD ( P < .001). 16 …”
Section: Introductionmentioning
confidence: 99%